Understanding farmers’ adaptation to climate change: A protection motivation theory application - Tina Sri Purwanti; Syafrial Syafrial; Wen-Chi Huang; Budi Hartono; Moh. Shadiqur Rahman; Jaisy Aghniarahim Putritamara (Cogent Social Sciences, 2023)
AbstractThis study examines the psychological determinants influencing farmers’ intentions to adapt to climate change through the lens of Protection Motivation Theory. This study uses cross-sectional data comprising 302 farmers in East Java, Indonesia, analyzed using a structural equation (SEM) model. The findings indicate that perceived risk and adaptation assessment positively impact perceived climate variability but negatively impact maladaptation. Meanwhile, perceived risk and adaptation assessment directly correlate with higher intention for adaptation. Intriguingly, adaptation assessment and perceived risk indirectly impact adaptation intention via perceived climate variability, although this influence is negative. Likewise, maladaptation emerged as a mediator variable, exerting a counteractive indirect impact on adaptation assessment. These findings suggest that farmers with a robust understanding of climate change are more inclined to adapt. Conversely, greater maladaptation diminishes the adaptation intention. This study recommends continuous implementation of adaptation strategies, coupled with more accessibility to climate information and extensions facilitated by governmental bodies. This multifaceted approach will raise awareness regarding climate change impacts, hence improving their adaptive practices.